Analysis of ServiceDesk Information System Success using Update DeLone and McLean Model Approaches - Yusuf Hendra Dwi Kusuma; Abdul Hakim; Ike Wanusmawatie (Wacana Journal of Social and Humanity Studies, 2021)
This research aims to analyze the success of the ServiceDesk Information System at Institut Teknologi Sepuluh Nopember (ITS) using An updated DeLone and McLean model approach. Data collection techniques are using questionnaires. The object of this research is the ITS ServiceDesk Information System. The subjects of this study are ITS Stakeholders, namely Lecturers, Students, Employees, and General Public, with a population of 1463 users, with 93 samples obtained from the Slovin technique. Analysis using Structural Equation Modeling (SEM) and Amos as a tool. The results showed that there was an influence between System Quality, Service Quality, and Information Quality on Use. Similarly, there are significant effects in System Quality, Service Quality, and Information Quality on User Satisfaction. Use is not affected by User Satisfaction because the System is Mandatory, this means the system is the only complaint system that exists without any other alternative. The significant influence is also shown by the Use and User Satisfaction with the greatest value on Net Benefits, this means that in an information system, User Satisfaction is proven to greatly affect the work of users, as well as the performance of the organization.